Different Mathematical Functions (Texas Journal of Multidisciplinary Studies, 2022)
This article about the production function of Cobb-Douglas is the technological ratio of the volume of labor resources and capital for the production of a certain amount of output. This model belongs to the two-factor model and was statically tested by the two Scientists Cobb and Douglas